2016
DOI: 10.1111/ijmr.12095
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Three‐Component Model of Relational Social Constructionist Leadership: A Systematic Review and Critical Interpretive Synthesis

Abstract: Given the increasingly acknowledged insight that people do not act as self-contained individuals but in relation to others and embedded in context, relational social constructionist leadership (RSCL) has recently gained exciting momentum. Unfortunately, this development has not been accompanied by sufficient efforts at clarification. This systematic concept-centric review, which consists of 47 empirical RSCL studies, contributes to a better understanding of RSCL as part of the relationality movement in leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 147 publications
(373 reference statements)
4
97
0
Order By: Relevance
“…Theoretical strands in the collective leadership literature include network leadership (Cullen‐Lester and Yammarino ), complexity leadership (Uhl‐Bien and Marion ), discursive leadership (Fairhurst ), and constructionist collective leadership (Drath ; Endres and Weibler ; Ospina et al ). They share a view of leadership as an emergent, interactive process intended to cultivate group members’ capacity and adaptability to navigate complexity.…”
Section: Leadership Studies and Public Leadership Scholarship: Towardmentioning
confidence: 99%
“…Theoretical strands in the collective leadership literature include network leadership (Cullen‐Lester and Yammarino ), complexity leadership (Uhl‐Bien and Marion ), discursive leadership (Fairhurst ), and constructionist collective leadership (Drath ; Endres and Weibler ; Ospina et al ). They share a view of leadership as an emergent, interactive process intended to cultivate group members’ capacity and adaptability to navigate complexity.…”
Section: Leadership Studies and Public Leadership Scholarship: Towardmentioning
confidence: 99%
“…They often originate in recent developments in general leadership theory, driven both by epistemological reorientations and empirical observations (cf Gronn, 2002;Cunliffe & Eriksen, 2011;Drath et al, 2006;Pearce & Conger, 2003;Raelin, 2011;Endres & Weibler, 2016). The traditional vertical leadership approaches as described in the above section are thus increasingly supplemented by approaches also including horizontal and thereby collective leadership.…”
Section: Horizontal Leaders and Their Leadershipmentioning
confidence: 99%
“…Relational leadership (Fletcher, 2004;Uhl-Bien, 2006;Cunliffe & Eriksen, 2011;Endres & Weibler, 2016) is closely connected to the notion of leadership as essentially a distributed phenomenon, emerging in interaction between people. It is usually described in contrast to 'entitative' perspectives in which the focus of interest is placed on the individuals interacting.…”
Section: Relational Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…When referring to "connections," Gittell (2016) advises "The energizing nature of high-quality connections serve as an endogenous resource for accomplishing work and for creating resilience in the face of stress" (p. 29). In their review of 47 Relational Social Constructionist Leadership (RSCL) empirical studies Endres and Weibler (2017) noted "we found that the content of emerging RSCL largely involves dimensions of highquality relating and communicating in terms of all the visible and invisible threads that connect people (in a largely positive sense)" (p. 225).…”
Section: An Integrated Relational Leading Practices Frameworkmentioning
confidence: 99%